3DWALKTHROUGH VIRTUAL REALITY (VR) UNTUK MEDIA PROMOSI PADA LAWANG SEWU SEMARANG BERBASIS WEB - Yuli Fitrianto; Toni Samkhaji (STEKOM PRESS, 2016)
Sector The development of information and communication technology is very fast resulting in changes in various aspects. 3D technology is now widely used in various ways, for example in making films, games, educational media and also promotional media. This type of 3D media promotion is very necessary to promote tourist attractions of historic buildings such as Lawang Sewu in Semarang which has beautiful architectural buildings. In addition to offline promotions using 2D media, 3D media are also considered quite effective if used as promotional media to eliminate the mystical and horror impressions of the people at Lawang Sewu. The solution offered in this study is the use of 3D Virtual Reality as a promotional tool that displays a virtual feel, where 3D promotions will be more interesting and look more real so that people will get a pleasant impression in visiting these tourist attractions. This research uses Research product development methods and Development (RnD), using 6 out of 10 stages of research namely potential and problems, data collection, product design, design validation, design improvement and product trials. The results of this study are to produce promotional aids by utilizing 3D VR technology. The validity value of media experts is 3.4 which is declared feasible, while the validity value of material experts is 3.2 which is declared feasible, and increases the audience's understanding and interest as a user from 33% up to 67%.